2012
DOI: 10.3109/14992027.2012.679747
|View full text |Cite
|
Sign up to set email alerts
|

Results from high-frequency hearing screening in 14- to 15-year old adolescents and their relation to self-reported exposure to loud music

Abstract: The observed failing rate compares well to findings on the prevalence of hearing deficits in adolescents reported in other studies. In addition, our study suggests that the risk for hearing damage from loud music is not steadily increasing with increase of exposure, but exists only under conditions of extreme listening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…In a cross-sectional study of 14- to 15-year-old students (n = 1294), those with 4 or more visits per month had a significantly higher risk of hearing loss, as compared to those with less exposure (24.5% vs 15.0%, P =.027). 33 Visits exceeding 4 hours duration trended toward worse hearing, but were not significantly different. A longitudinal follow-up study (n = 106 adolescents) stratified risk with a more generalized measure of exposure frequency and found that those with hearing loss were significantly more likely to self-report “medium” as opposed to “rare” or “no” total music exposure ( P < .001, girls and boys), “medium” to “frequent” live concert attendance ( P < .06, boys), “frequent” attendance at discos ( P < .009, girls), and “high” exposure to music at home ( P <.012, girls).…”
Section: Impact Of Noise Exposure On Pediatric Hearing Lossmentioning
confidence: 84%
“…In a cross-sectional study of 14- to 15-year-old students (n = 1294), those with 4 or more visits per month had a significantly higher risk of hearing loss, as compared to those with less exposure (24.5% vs 15.0%, P =.027). 33 Visits exceeding 4 hours duration trended toward worse hearing, but were not significantly different. A longitudinal follow-up study (n = 106 adolescents) stratified risk with a more generalized measure of exposure frequency and found that those with hearing loss were significantly more likely to self-report “medium” as opposed to “rare” or “no” total music exposure ( P < .001, girls and boys), “medium” to “frequent” live concert attendance ( P < .06, boys), “frequent” attendance at discos ( P < .009, girls), and “high” exposure to music at home ( P <.012, girls).…”
Section: Impact Of Noise Exposure On Pediatric Hearing Lossmentioning
confidence: 84%
“…Taking into account a high rate of environmental exposures among teenagers and young adults, much attention was paid to the prevalence of NIHL and NIT in the younger groups of subjects. Although no significant increase in NIHL was observed, the rate of noise-induced threshold shift was significantly higher in adolescents with high exposure to music[ 5 ] and in young females. [ 6 ] The latter finding may reflect the increased exposures of young women to recreational noise.…”
Section: Noise-induced Hearing Lossmentioning
confidence: 99%
“…Similar times of exposure expressed in hours per week were shown by other studies [ 45 , 46 ]. Only one study provides more a conservative value of 4 h per week [ 47 ]. The literature data shows also that the critical limit for the safety of exposure to loud sounds of music is L eq , 8 h of 80 dBA [ 46 ], and the hearing effects of using PLDs could be most clearly seen after five years of exposure [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%